(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2020)
While it may at first sight seem strange that Kant decides to spend seven pages of the third Critique discussing jokes and laughter, it would be a mistake to conclude that these considerations are irrelevant to his aesthetic theory and general philosophical goals. Laughter at humour is an important and meaningful human experience, worthy of attention and philosophical analysis. In particular, then, I maintain that laughter in response to humour does not, on Kant’s view, count as a pure aesthetic judgment. But, I argue, if one grants that laughter at humour can lead to a pure aesthetic judgment, the judging in response t​o a humorous joke would be analogous, but not identical, to the experiences of the sublime and the beautiful. Finally, I argue that humour-elicited laughter, as a play with aesthetic ideas and thoughts, is of interest to reason since offers a hint of reason’s activity in the sensible world.